Bone and Cartilage Demonstrate Changes Localized to Bone Marrow Edema-like Lesions within Osteoarthritic Knees - Kazakia, Galateia J (2012)
OBJECTIVE: Our objective is to understand the biological and mechanical pathways linking cartilage, bone, and marrow changes in the progression of osteoarthritis (OA). The aim of the present study was to evaluate bone structure and composition within bone marrow edema-like lesion (BMEL) regions associated with knee OA. METHODS: Tibial plateau specimens (n = 18) were collected from 10 subjects with knee OA scheduled for total knee arthroplasty (TKA). Magnetic resonance (MR) imaging was used to identify BMEL and quantify metrics of cartilage composition. Micro-computed tomography (μCT) and high-resolution peripheral quantitative computed tomography (HR-pQCT) were used to quantify density and microstructure of the subchondral trabecular bone. Fourier transform infrared (FTIR) spectroscopy was used to quantify tissue composition. RESULTS: Trabecular bone within BMEL was higher in volume fraction, with more and thicker trabeculae that were more plate-like in structure compared to unaffected regions. BMEL trabecular tissue composition had decreased phosphate and carbonate content. Marrow infiltration by a fibrous collagen network and evidence of increased bone remodeling were present. Structural and compositional changes were specifically localized to regions underlying cartilage degradation. CONCLUSION: These results support the paradigm of focal interactions among bone, marrow, and cartilage in the progression of knee OA. Quantitative evaluation of tissue changes and interactions may aid in the understanding of disease pathophysiology and provide imaging markers for disease progression.